Study the effect of operation parameter for monoethanolamine (mea) wastewater treatment using activated carbon, chitosan and rice husk - Nurul Asmawati, Roslan (2013)
Absorption of carbon dioxide (CO2) technology by Monoethanolamine (MEA) is widely used in oil and gas industry. Upon usage, the MEA is contaminated with hydrocarbon and suspended solids. Heavily contaminated MEA solution reduces its effectiveness in stripping the CO2 gas and also causes foaming phenomenon in the CO2 removal unit which further reduces the overall performance of the unit. Due to that, MEA is discharge from the industry as wastewater. This research is conducted to evaluate the feasible methods to recycle and reuse the monoethanolamine (MEA) wastewater while maintaining the amine concentration level via adsorption process. Adsorption method is used for the treatment with three different types of adsorbent which are activated carbon, chitosan and rice husk. Two different variables, namely adsorbent dosage and circulation time are varied to examine the effects on the parameters which are percentage of residue oil and amine concentration. Activated carbon showed the best performance among these three adsorbent. Application of activated carbon resulted in 95 % reduction in residue oil at 6.5 hours of contact time. Chitosan reduced the residue oil up to 90 % and rice husk 71 %. These three adsorbents were able to maintain the MEA concentration by percentage loss below than 9 %